AN OPTIMIZED GALLIUM NITRIDE (GAN)-BASED BIDIRECTIONAL DUAL-ACTIVE-BRIDGE CONVERTER FOR HIGH-EFFICIENCY ELECTRIC VEHICLE FAST-CHARGING STATIONS - Sutikno Wahyu Hidayat; Ferdy Hendarto; Pompy Pratisna (Journal of Moeslim Research Technik, 2026)
Rapid expansion of electric vehicle adoption has intensified the demand for high-efficiency fast-charging stations capable of delivering reliable, compact, and bidirectional power conversion while supporting renewable energy integration and vehicle-to-grid applications. Conventional silicon-based converters increasingly face limitations related to switching losses, thermal management, and power density under high-frequency operation. This study aimed to develop and validate an optimized Gallium Nitride (GaN)-based Bidirectional Dual-Active-Bridge (DAB) converter to improve conversion efficiency, thermal performance, and operational flexibility for electric vehicle fast-charging infrastructure. Quantitative engineering research employing mathematical modeling, simulation, optimization, prototype development, and experimental validation was conducted using MATLAB/Simulink, PLECS, and laboratory measurements under representative charging and discharging conditions. Performance indicators included conversion efficiency, switching losses, thermal characteristics, voltage regulation, power density, and dynamic response. Experimental results demonstrated a maximum conversion efficiency of 98.74%, a 51.85% reduction in switching losses, a 73.33% increase in power density, significantly lower operating temperatures, improved voltage regulation, and stable bidirectional power transfer across broad operating conditions. Statistical analysis confirmed significant improvements over conventional silicon-based converter configurations. Integrated optimization of GaN semiconductor devices, adaptive phase-shift modulation, high-frequency transformer design, and digital control collectively produced substantial system-level performance enhancement. Findings indicate that the proposed converter provides a technically robust and energy-efficient solution for next-generation electric vehicle fast-charging stations, supporting sustainable transportation, intelligent energy management, and future smart-grid integration.